Development and evaluation of themostabilized multiplex polymerase chain reaction for simultaneous detection of klebsiella pneumoniae and haemophilus influenzae - Khazani, Nur Amalina (2016)
Klebsiella pneumoniae and Haemophilus influenzae are important pathogens associated with the various types of infections such as pneumonia, respiratory tract infections, meningitis and also septicemia. The identification of these pathogens using culture methods are time-consuming, and insensitive, while conventional polymerase chain reaction (PCR) still require cold-chain storage and trained personnel to perform the assay. Thus, the aim of this study is to develop and evaluate the thermostabilized multiplex PCR for simultaneous detection of K. pneumoniae and H. influenzae. Three sets of primer, php gene of K. pneumoniae, p6 gene of H. influenzae and glmM gene of Helicobacter pylori (internal control) were designed and optimized in this study. All PCR reagents such as Taq DNA polymerase, MgCI2, dNTPs, 10 X buffer and primers were optimized and lyophilized into a pellet form with an enzyme stabilizer (trehalose). The concentrations of enzyme stabilizer and Taq DNA polymerase were optimized for thermostabilized multiplex PCR. The analytical sensitivity of the assay was evaluated both at the genomic and bacteria levels. While, the analytical specificity of thermostabilized multiplex PCR was evaluated using 30 different bacteria. The stability of thermostabilized multiplex PCR was determine using accelerated stability test at three different temperatures (4°C, 25°C, and 37°C). The results showed that thermostabillized PCR was stable at the concentrations of 8% stabilizer and 200% Taq DNA polymerase. The limit ofdetection (LOD) at genomic level for multiplex K. pneumoniae and H. influenzae was 1 pg of DNA. On the other hand, the LOD at bacterial level multiplex PCR of K. pneumoniae and H. influenzae was 1 x 103 CFU/ ml. The thermostabilized multiplex PCRs demonstrated specificity of 100% with no amplification was observed with other bacteria strains. Based on the stability tests, the thermostabilized multiplex PCR was estimated to be stable for at least 3.02 months at 25°C. The thermostabilized multiplex PCR for detection of K. pneumoniae and H. influenzae is simple, specific, easy to perform, cost-effective and minimize the preparation time of PCR mixture. Hence, this assay has potential to be used in routine diagnosis, hospital settings and fields